Legal Challenges in Enforcing the Duty to Render Assistance at Sea: Implications for Maritime Autonomous Surface Ships (MASS) - Hasan, Sabrina (Journal of Legal Studies, 2025)
International Shipping is subject to both national and international regulations to ensure safe and sound shipping as well as to enforce rights and obligations. Technological advancement in the shipping industry especially the introduction of maritime autonomous surface ships (MASS) is going to bring a great change along with challenges. Moreover, there are issues concerning the regulation of MASS under existing regimes such as the meaning of the relevant terms, the requirement to have a master and crew on board, the master’s duty to render assistance at sea, seaworthiness and avoidance of collisions. This paper aims to focus on the enforcement of the duty to render assistance at sea over MASS. Hence, this paper analyses the challenges that may arise while employing the duty over MASS, non-compliance under the present laws and the need for the adoption of a new regulatory framework to settle such non-compliances.